2020
DOI: 10.3390/su12041393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SOP Lagoon Additive on Gaseous Emissions from Stored Liquid Dairy Manure

Abstract: Animal manure is a source of greenhouse gas (GHG) emissions and other pollutants and nuisances such as ammonia and odors. There are several technologies to reduce emissions on animal farms including manure additives; however, few have been proven effective and easy to apply to dairy lagoon systems. The present research aimed at testing the ability of the commercial additive “SOP LAGOON” to reduce emissions of GHGs (i.e., carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O)), as well as ammonia (NH3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
2
1
Order By: Relevance
“…However, a synergistic effect of the components in SOP has never been researched for CH 4 mitigation. Borgonovo et al (2019) and Peterson et al (2020) [31,32] found that gypsum processed with SOP's proprietary technology reduced NH 3 and GHG emissions in liquid manure with a much lower dosage of gypsum than reported previously [33]. However, this same effect with low doses was not seen in the current study.…”
Section: Effects On Enteric Emissionscontrasting
confidence: 56%
“…However, a synergistic effect of the components in SOP has never been researched for CH 4 mitigation. Borgonovo et al (2019) and Peterson et al (2020) [31,32] found that gypsum processed with SOP's proprietary technology reduced NH 3 and GHG emissions in liquid manure with a much lower dosage of gypsum than reported previously [33]. However, this same effect with low doses was not seen in the current study.…”
Section: Effects On Enteric Emissionscontrasting
confidence: 56%
“…Borgonovo et al first tested the gypsum-based commercial additive, "SOP LAGOON, " on fresh dairy manure and found the additive to be effective in reducing direct NH 3 and GHG emissions, including a significant mitigation of CH 4 emissions (Borgonovo et al, 2019). Recent literature by Peterson et al applied SOP Lagoon to liquid stored dairy cattle manure over a 2 week period and found similar results including significant reductions in NH 3 emissions (22.7% for the supplemented systems as compared with an unsupplemented control) (Peterson et al, 2020). With the strong literature documenting the potential for gypsum to decrease CH 4 emissions, this seems like a viable manure amendment strategy.…”
Section: Mitigation Strategies For Dairy Cow Manure Gas Emissionsmentioning
confidence: 91%
“…All emission measurements were done in triplicate, in separate flux chambers, and on site. Previous studies have used this flux chamber method to measure manure emissions (Joo et al., 2012; Park et al., 2010; Peterson et al., 2020; Sun et al., 2014).…”
Section: Methodsmentioning
confidence: 99%